PENERAPAN MODEL INKUIRI TERBIMBING BERBANTUAN PHET SIMULATIONS UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH PADA MATERI TEKANAN ZAT CAIR - Santoso, Nur Rasyid Bagus; Widodo, Wahono (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aimed to describe the implementation of learning, problem solving skills, and students' responses to the implementation of the guided inquiry learning model assisted by PhET Simulation on liquid pressure material at MTs City of Surabaya. The research method uses descriptive quantitative research using pre-experimental methods and a sample of 36 students. This research design uses One Group Pretest-Posttest Design. The data collection technique used observation, test, and questionnaire methods with instruments including learning implementation observation sheets, test sheets, and response questionnaire sheets. The results of this study, namely (1) the implementation of all learning using guided inquiry assisted by PhET Simulations is very well implemented with an average percentage of 81%; (2) the problem solving skills of students who have applied guided inquiry assisted by PhET Simulations get an average n-gain of 0.5 with moderate criteria; and (3) students respond positively well by obtaining an average percentage of 77% in the strong category of applied learning.